COVID-19 and the veterinarian performance in the context of One Health (Research, Society and Development, 2020)
The objective was to report the forms of intervention of the Veterinary Doctor to COVID-19 in the context of One Health. An integrative review of a qualitative and quantitative character was performed in the databases: Google Scholar, SciELO, PubMed and Lilacs, in Portuguese and English, between May and July 2020, according to the descriptors COVID-19, SARS-CoV -2, One Health and Medicine Veterinary. In addition to clinical assistance, veterinary practice is directly involved in areas of human and environmental protection, such as: health surveillance actions, inspection of products of animal origin and studies by COVID-19 and the like. It works in the development of vaccines and their use protocol, in the release of material and professionals for health actions, in addition to the adaptation of its laboratories for human use. It is up to him to study virulence factors in animal models and to be involved in the formulation of policies and measures for the management of live animal markets. It is concluded that veterinarians are properly trained to act in the face of a pandemic scenario, especially that of COVID-19, which is a zoonosis of etiological agent studied for several years.